Study of polarization diversity circuit in silicon photonics - Lee, Tze Jun. (2009)
A light source can be broken down into its electric field vectors; the Transverse Electric (TE) and the Transverse Magnetic (TM). Structural birefringence causes the high frequency TE and TM waves to travel at different speeds. This causes the waves to arrive at their destinations with a phase difference resulting in loss of power or bit error rate in data transmissions. Hence, current optical circuits are limited to a frequency of 40Gbps.